Adapting to Climate Risk? Local Population Dynamics in the United States - Agustín Indaco; Francesc Ortega (Institute of Labor Economics (IZA), 2023)
Using a new composite climate-risk index, we show that population in high-risk counties has grown disproportionately over the last few decades, even relative to the corresponding commuting zone. We also find that the agglomeration is largely driven by increases in the (white) working-age population. In addition, we show that high-risk tracts have typically grown more than low-risk tracts within the same county, suggesting the presence of highly localized amenities in high-risk areas. We also document heterogeneous population dynamics along a number of dimensions. Specifically, population has been retreating from high-risk, low urbanization locations, but continues to grow in high-risk areas with high residential capital. The findings above hold for most climate hazards. However, we document that tracts with high risk of coastal flooding have grown significantly less than other tracts in the same county.
Keywords: J3; J7; 330; climate risk; agglomeration; migration